Influence of attributional style, anger, and self-control on college students’ impulsive consumption - Zhou, Guohua; Sun, Wentao; Qu, Weiguo (Frontiers in Psychology, 2025)
IntroductionWith the rapid development of the digital economy and the prevalence of consumerism in recent years, impulsive consumption among college students has become increasingly prominent, a phenomenon closely associated with their psychological traits and emotional states. Even though research has examined self-control and consumption, few studies have integrated attributional style. Therefore, this study systematically examines the effects of attributional style, anger, and self-control on impulsive consumption behaviors among college students through three experiments.MethodsUndergraduate participants were recruited from a university in Changsha, China. Experiment 1 investigated the impact of attributional style on impulsive consumption. Experiment 2 explored the interactive effects of anger and attributional style on impulsive consumption. Finally, Experiment 3 further examined the interaction between self-control and attributional style.ResultsExperiment 1 found that participants with optimistic attributional styles exhibited significantly lower levels of impulsive consumption than those with pessimistic attributional styles. Experiment 2 revealed that anger significantly suppressed impulsive consumption behaviors and interacted with attributional style. Experiment 3 demonstrated that higher levels of self-control effectively reduced impulsive consumption and produced significant interactive effects with attributional style.DiscussionThese findings indicate that optimistic attributional styles, anger induction, and high self-control significantly inhibit impulsive consumption among college students. These results provide novel theoretical insights into the psychological mechanisms underlying impulsive consumption in this population and offer empirical support for targeted psychological interventions in consumer behavior.